Involvement of Abscisic Acid in Transition of Pea (Pisum sativum L.) Seeds from Germination to Post-Germination Stages - Smolikova, Galina; Krylova, Ekaterina; Petřík, Ivan; Vilis, Polina; Vikhorev, Aleksander; Strygina, Ksenia; Strnad, Miroslav; Frolov, Andrej; Khlestkina, Elena; Medvedev, Sergei (Plants (Basel, Switzerland), 2024)
The transition from seed to seedling represents a critical developmental step in the life cycle of higher plants, dramatically affecting plant ontogenesis and stress tolerance. The release from dormancy to acquiring germination ability is defined by a balance of phytohormones, with the substantial contribution of abscisic acid (ABA), which inhibits germination. We studied the embryonic axis of Pisum sativum L. before and after radicle protrusion. Our previous work compared RNA sequencing-based transcriptomics in the embryonic axis isolated before and after radicle protrusion. The current study aims to analyze ABA-dependent gene regulation during the transition of the embryonic axis from the germination to post-germination stages. First, we determined the levels of abscisates (ABA, phaseic acid, dihydrophaseic acid, and neo-phaseic acid) using ultra-high-performance liquid chromatography-tandem mass spectrometry. Second, we made a detailed annotation of ABA-associated genes using RNA sequencing-based transcriptome profiling. Finally, we analyzed the DNA methylation patterns in the promoters of the PsABI3, PsABI4, and PsABI5 genes. We showed that changes in the abscisate profile are characterized by the accumulation of ABA catabolites, and the ABA-related gene profile is accompanied by the upregulation of genes controlling seedling development and the downregulation of genes controlling water deprivation. The expression of ABI3, ABI4, and ABI5, which encode crucial transcription factors during late maturation, was downregulated by more than 20-fold, and their promoters exhibited high levels of methylation already at the late germination stage. Thus, although ABA remains important, other regulators seems to be involved in the transition from seed to seedling.
Keywords: embryonic axis; DNA methylation; ABA-associated genes; seed-to-seedling transition; Pisum sativum L.; abscisic acid